Starting up transition management: A closer view on the systems analysis and how it initiated transformative thinking in Ghent and Aberdeen cities. - Maas, Suzanne; Fortuin, Karen; Frantzeskaki, Niki; Roorda, Chris (Springer, 2018)
This chapter presents a systems analysis methodology for the first phase of Transition Management, the preparation and exploration phase, in an urban context. The methodology consists of the following four steps, which are followed in an iterative way: (i) system definition, (ii) system structuring, (iii) data gathering and (iv) data assessment and analysis. Characteristic of this methodology is the use of the SCENE sustainability model, in combination with a set of lenses that reflect a variety of ways of looking at the system from macro, meso, and micro level. Together, these lenses ensure an integrated perspective and thorough analysis of a city's government and governance. The systems analysis methodology was applied in the cities of Ghent and Aberdeen to identify the challenges and opportunities in their cities with respect to energy use and CO2 reductions. The outcomes and reflections on their respective systems analyses show that creating an overview of the state of the system revealed interesting connections and that constructing a historical analysis of the city inspired and motivated participants. The systems analysis broadened the problem perception, revealed institutional barriers to sustainable development and served as a catalyst for mutual understanding and learning between the participants. Overall, the systems analysis methodology proved to be an effective method to create an overview of the city activities under study, and stimulated the creation of a common information base and holistic thinking amongst participants in the transition process.
Keywords: Nachhaltige Stadtentwicklung; Kooperation; Akteur; Transformation; Umwelt; Flächennutzung; Ressourcen; Lebensqualität; Städtevergleich; Systemanalyse; Datenanalyse